Proses Divestasi Saham Berdasarkan Undang-undang Nomor 3 Tahun 2020 - Gebika Raseuki (Pusat Riset dan Inovasi Nasional, 2025)
In Article 112 of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining, there are provisions that require mining companies to sell a portion of their shares to the government or State-Owned Enterprises (BUMN). This obligation aims to control the exploitation of natural resources, enhance the state's control over strategic mineral and coal resources, and promote the sustainable utilization of natural resources. This journal comprehensively reviews the legal processes and implementation of the nationalization of share divestment, including potential challenges that may arise and their impact on the mining industry in Indonesia. The journal provides valuable insights into how this law governs vital natural resources for the country and contributes to the discourse on granting rights and state control over the extractive sector, with significant implications for mining policies in Indonesia and the potential for improved natural resource management.